Persepsi Masyarakat Terhadap Pemanfaatan Ruang Terbuka Publik di Kota Masohi (Studi Kasus Koridor Jalan Pattimura Kota Masohi) - Indayanni Namakule Namakule; Andia Nurhaeny; Adnan Affan Akbar Botanri (Lembaga Intelektual Muda Maluku, 2025)
This study aims to understand the community's perception of the utilization of the Public Open Space at Koridor Jalan Pattimura, Masohi City, which is located in a strategic area. The research uses a qualitative method, with descriptive analysis and Behavioral Mapping to analyze the activity patterns of visitors at Koridor Jalan Pattimura. Data collection techniques include observation, semi-structured interviews, questionnaires, and documentation. The results show that the most dominant activity pattern in Koridor Jalan Pattimura is gathering (33%), followed by exercise (17%), walking (12%), relaxing (10%), socializing (8%), cleaning (7%), playing (5%), refreshing (5%), and street vendors (3%). The most common activities are gathering, exercising, walking, socializing, and other social activities. Despite the available supporting facilities, most of them are not functioning properly and are already damaged. Therefore, the utilization of public open space for visitor activities requires government intervention to address issues related to security for those engaging in activities